2021
DOI: 10.1155/2021/5572569
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Ion Release and Alkalizing Potential of Three Bioactive Dental Materials in Comparison with Composite Resin

Abstract: Aim. Several new bioactive compounds were recently introduced to the market with favorable ion release, tooth remineralization, and alkalizing potential. This study sought to compare the phosphate ion release and alkalizing potential of three bioactive materials in comparison with composite resin. Methods. Thirty-six discs (2 × 6 mm) were fabricated from Fuji II LC resin modified glass ionomer (RMGI), Activa BioActive, Cention N, and Z250 composite in plastic molds. The specimens were stored in distilled water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“… 30 A recent study found that that phosphate ions increased over time more than glass ionomer. 31 These findings are in agreement with our results and may explain the highest reading recorded of Ca:P ratio and KHN in the Activa BioActive-Restorative group, which may translate into providing the highest remineralisation potential, among other materials.…”
Section: Discussionsupporting
confidence: 92%
“… 30 A recent study found that that phosphate ions increased over time more than glass ionomer. 31 These findings are in agreement with our results and may explain the highest reading recorded of Ca:P ratio and KHN in the Activa BioActive-Restorative group, which may translate into providing the highest remineralisation potential, among other materials.…”
Section: Discussionsupporting
confidence: 92%
“…The results are in accordance with Gupta et al who found that Cention-N (selfcure) has more fluoride ion release and alkalizing capability in acidic pH as compared to Cention-N (light-cure) and GIC 25 . The results are in consistent with Kasraei et al who reported Ca and p ion release from activa bioactive composite and Cention N and concluded that these bioactive materials can have a long term positive effect on tooth remineralization 26 . The results also in accordance with Tiskaya et al 27 who reported ion release from Activa Bioactive and Cention_N which varies according to the pH of the immersion medium.…”
Section: Discussionsupporting
confidence: 91%
“…The LCTE of resin-based materials is affected by the amount of filler [40]. Beautifil flow plus has a 47 vol% of filler [41], RMGI has 55 vol% filler [28], and alkasite has a 58 vol% (78 wt%) filler content in the final mass [28,42]. Thus, the harsh oral environment could not be simulated, which is a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference among various pH conditions. It is assumed that alkasite has high alkalizing potential with the release of hydroxyl ions [28]. Kasraei S et al reported that the RMGI and alkasite showed a significant increase in the pH following acidification of the environment [28].…”
Section: Discussionmentioning
confidence: 99%